2007
DOI: 10.1083/jcb.200701006
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 regulates cell polarization and directional migration through Src kinase and Rho GTPases

Abstract: Development, angiogenesis, wound healing, and metastasis all involve the movement of cells in response to changes in the extracellular environment. To determine whether caveolin-1 plays a role in cell migration, we have used fibroblasts from knockout mice. Caveolin-1–deficient cells lose normal cell polarity, exhibit impaired wound healing, and have decreased Rho and increased Rac and Cdc42 GTPase activities. Directional persistency of migration is lost, and the cells show an impaired response to external dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
362
2
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(404 citation statements)
references
References 64 publications
33
362
2
7
Order By: Relevance
“…Nevins and Thurmond demonstrated the interaction between caveolin-1 and Cdc42 [50]. Further studies also revealed a role in the activation and regulation of Rho, suggesting a role of caveolin-1 in cell polarity and migration [51]. del Pozo et al [52] reported that lipid rafts are involved in signal transduction events initiated by cell adhesion to the extracellular matrix, which is mediated by integrins.…”
Section: Proteins Associated With Lipid Rafts and Caveolaementioning
confidence: 99%
“…Nevins and Thurmond demonstrated the interaction between caveolin-1 and Cdc42 [50]. Further studies also revealed a role in the activation and regulation of Rho, suggesting a role of caveolin-1 in cell polarity and migration [51]. del Pozo et al [52] reported that lipid rafts are involved in signal transduction events initiated by cell adhesion to the extracellular matrix, which is mediated by integrins.…”
Section: Proteins Associated With Lipid Rafts and Caveolaementioning
confidence: 99%
“…8 Cav1 Y14 has also been shown to promote cell polarization and directional migration in mouse embryonic fibroblasts by enabling Src-mediated RhoGTPase activity. 39 More recently, we showed that tyrosine-phosphorylated Cav1 functions as an effector of Rho/ROCK signaling in the regulation of FA turnover, defining a feedback loop between Rho/ROCK, Src and phosphorylated Cav1 in tumor cell migration. 41 …”
Section: The Galectin Lattice: Master Control Machinery Of Plasma Memmentioning
confidence: 99%
“…40 Gal-3-mediated integrin activation therefore acts through pY14Cav1 to induce a membrane organization within FA that restricts exchange of FAK and other FA components and enables FA turnover. In two additional studies, pY14Cav1 has been shown to recruit Csk, thereby inhibiting Src activity and leading to a p190RhoGAP-dependent increase in RhoGTP levels; 39 this regulates the localization of pY14Cav1 to cell protrusions as well as the dynamics of FAK at focal adhesion sites, and thus influences tumor cell migration. 41 Thus, pY14Cav1 sufficiently stabilizes FA components at FA sites to allow FA maturation, substrate adherence at cellular protrusions, and directional motility.…”
Section: Concerted Regulation Of Focal Adhesion Dynamics By Tyrosine mentioning
confidence: 99%
See 1 more Smart Citation
“…Cav-1 possesses a 'scaffolding domain' that interacts with signal transduction molecules [11]. Not only is this domain required to form multivalent homo-oligomers with other cav proteins, but it also mediates the interaction of cav-1 with non-cav proteins, such as the G-subunits, Ha-Ras, Src family kinases and eNOS [12][13][14][15]. Consequently, cav-1 acts as molecular 'Velcro' where signal transduction complexes are bound in the inactivated state [16].…”
Section: The Lipid Raft Hypothesismentioning
confidence: 99%